Backward Design Untuk Efektifitas Pelatihan Kaderisasi Pengurus di Pondok Pesantren Nurul Jadid - Azharghany, Rojabi; Muhammad Ibtida Unniam (Pencerah, 2023)
The use of learning design models, such as backward design, has become an effective choice for educational and cadre institutions in designing effective and targeted training programs. Nurul Jadid Islamic Boarding School, an Islamic educational institution which has an important role in spreading religious values, education, cadre formation, da'wah and community service, can utilize backward design to increase the attractiveness and visibility of the management cadre training program. Currently, the implementation of the cadre training program for administrators in Islamic boarding schools is still experiencing various obstacles, including: training materials that are not on target, lack of interest from administrators in participating in cadre development training and training that does not produce the expected output and outcomes. Furthermore, this service program was carried out to solve this problem, by focusing on implementing the backward design model in designing a cadre training program for Nurul Jadid Islamic Boarding School administrators that was effective and right on target. The service method used is participatory action research (PAR) so that the administrators who are accompanied can implement sustainability. The result of this service activity is that through the application of the backward design approach and the PAR method, the administrator cadre training program at the Nurul Jadid Islamic Boarding School was able to achieve the goals of effectiveness, relevance and sustainability.